Process for producing ferulyl-substituted acylglycerols for use as novel sunscreen agents - Lai, Oi Ming; Lo, Seong Koon (2007)
A relatively cheap process for producing ferulyl-substituted acyglycerols is provided by which involves esterifying some or all of the free fatty acids of deodoriser distillates obtained from the processing and refining of edible fats and oils and ferulic acid with glycerol. Separation and removal methods are performed to obtain a purified ferulyl-substituted acyglycerol product.